A regressive model for dynamic instabilities during the condensation of R404A and R507 refrigerants. (October 2019) - Kuczynski, Waldemar; Bohdal, Tadeusz; Meyer, Josua P.; Denis, Aleksander
Highlights: Evolution and disappearance of condensation of R507A refrigerant in pipe mini-channels. Condensation process occurring in mini-channels. Comparison of the results of experimental studies with R404A obtained for R507A. Proposition of a regression function for the description of dynamic instability. Abstract: This paper presents the results of experimental research and mathematical modelling on the influence of dynamic instabilities on the condensation phase change of R507 refrigerant in tubular mini-channels. This agent is currently being utilised as a temporary substitute for R404A, with R448A intended as the target substitute. In addition to the results, this paper contains a dimensional analysis procedure based on the Π-Buckingham theorem that has allowed for the development of a regressive model for the velocities of the dynamic instabilities. The experimental part of this paper was conducted using tubular mini-channels with internal diameters of 1.44, 2.3, and 3.3 mm.